Leasing from the perspective of environmental management and its influence on business performance - Bocok, Vojtech; Hinke, Jana; Abrham, Josef (Frontiers in Environmental Science, 2023)
The paper aims to analyze the current development in the field of circular economy relating to the use of lease financing. The introduction of the paper specifies views associated with the application of principles of circular economy and its use in current conditions, when there is greater pressure to apply environmental measures in the long-term business behavior. First, the possibilities of approaching leases as a product supporting the principles of circular economy are described, which is then followed by describing the current state of research in this area. The paper contains own research conducted on companies trading on the Prague Stock Exchange in the period from 1993 to 2019, in which the influence of lease financing on market values of companies representing investor confidence and subsequently profitability ratios are examined. Companies using lease financing and those not using it are compared. The research uses a regression model of panel data. The last part of the paper presents the research results together with a discussion, where the results are compared with another similar study.